The Impact of Learning Counseling Services Utilizing Discussion Techniques to Mitigate Learning Difficulties Among Students in Vocational High Schools - Indah Fajriani; Zahara Assyfa; Oki Dermawan; Kissisina Umahdi (Educatio, 2025)
Learning difficulties are conditions in educational contexts characterized by specific barriers that impede the achievement of learning outcomes. This issue is experienced by tenth-grade students at the Yayasan Pendidikan Panjang Vocational High School in Bandar Lampung, including (a) low academic performance, (b) students' slow pace in completing assignments, and (c) students exhibiting unusual attitudes such as indifference and pretense.  The objective of this study is to assess the effect of learning counseling services that employ discussion techniques to reduce accounting learning difficulties among students at the Yayasan Pendidikan Panjang Vocational High School in Bandar Lampung. This research adopts a pre-experimental design, specifically a one-group pretest-posttest design. The population for this study comprises 26 students, with a sample size of 8 students selected through purposive sampling techniques. The findings indicate that the pretest scores yielded a total of 909, with a mean value of 113, while the posttest scores amounted to 552, corresponding to a mean of 69. The difference between pretest and posttest scores is calculated to be 44, with an average difference of 1.63. A non-parametric Wilcoxon test conducted using SPSS version 25 revealed a Z-value of -2.527, with an Asymptotic Significance (2-tailed) of 0.012. Since the value of 0.012 is lower than the threshold of 0.05, we reject the null hypothesis (H0) and accept the alternative hypothesis (Ha). Consequently, there is a statistically significant difference between the pretest and posttest results, leading to the conclusion that learning counseling services employing discussion techniques effectively reduce accounting learning difficulties among students at the Yayasan Pendidikan Panjang Vocational High School in Bandar Lampung.